Fidelity of the film adaptation of the novel "Fifty shades of grey" - Billones, Toni Rose D.
This undergraduate thesis is a critical analysis of film adaptation Fifty Shades of Grey to find out its fidelity to the novel in terms of character, setting, and plot using the Theory of Adaptation by Linda Hutcheon and the interpretation of film adaptations by John Desmond and Peter Hawkes. This study highlights the characteristics of the film as a medium especially when it is adapted from a literary work and serves as a guide to filmmakers in adapting literary works. It recommends that film producers should work with the author to create a more faithful adaptation especially to novel series like Fifty Shades. The analysis uses a codebook designed to allow cues to be counted and tallied to determine the elements carried over in the film adaptation. The researchers conclude that the film Fifty Shades of Grey is an intermediate adaptation of the novel with certain narrative elements specifically the character, setting and plot, undergoing addition or deletion in the adaptation process. The dropping of some characters caused a domino-effect on the other elements such as the setting and plot events. The film adaptation changed the mood of the story, from a very explicit into a more subtle form, by adding scenes that can be categorized as romantic rather than sensual.